Effects of two work-to-rest ratios on physiological, neuromuscular, and RPE responses during taekwondo-specific HIIT - Zheng, H.; Zhang, G.; Zhong, Y.; Yin, M.; Gu, Z.; Wang, X.; Zeng, X.; Nassis, G. P.; Li, Y. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Purpose To investigate the effects of different work: rest (W: R) ratios on physiological, neuromuscular, and rating of perceived exertion (RPE) responses during taekwondo-specific high-intensity interval training (HIIT).